Psychoeducation: The Role of Parents in Improving Motor Skills and Understanding Emotional State of Cerebral Palsy Children Using Flash Cards - Ramadhanti, Bella; Elisabeth, Mary Philia (Eduvest - Journal of Universal Studies, 2023)
Cerebral Palsy (CP) is a chronic motor disorder resulting from non-progressive damage to brain development, exhibiting various clinical disorders with unknown causes. This research focuses on a severe case of CP in a student named Prisil, investigating the challenges she faces in motor and language skills development. Prisil's parents and teachers play a crucial role in addressing these challenges. The study, employing a qualitative case study approach, utilizes psychological tests and interventions to understand and enhance Prisil's abilities. The intervention plan targets parental knowledge, language improvement, and teacher support. Prisil's developmental history, challenges, and interventions are explored, emphasizing the need for structured learning environments. The findings contribute insights into optimizing motor and language skills in children with CP, enhancing their overall well-being and fostering independence.